Performance of fuel-air combustion in a reheating furnace at different flowrate and inlet conditions. (1st September 2020) - Liu, Yiwei; Wang, Jin; Min, Chunhua; Xie, Gongnan; Sundén, Bengt
Abstract: A geometry model for simulating the gas circulation, heat transfer and slab heating process in a reheating furnace was developed with numerical simulation. The slabs are heated in the furnace and the temperature of the slabs become above more than 1500 K, and then they are transported to the rolling mill. The slab heating in a reheating furnace is influenced by many factors, such as gas velocity, the movement speed of the slab, the height and spacing of the burners and others. The slab heating characteristics in the walking beam type reheating furnace were studied by considering the slab movement. The movement of the slabs was processed by transferring temperature data from the previous location to the next location. It was assumed that no time is spent for moving the slabs. Especially, the effects of different inlet boundaries of the burners were investigated. Results show that the entrainment effect from the inner air flow results in a larger coverage area of the flames, and there is an increase of more than 28.5% in the slab temperature over the whole furnace. Highlights: Unsteady simulations of heating characteristics of slabs were performed in a furnace. Increasing burner fuel flow rate cannot obtain uniform temperature distribution. The slab temperature increases by more than 28.5% due to an entrainment effect. Air released from the inner central passage can reduce the emissions of CO2 and CO.